Kafka educador: um estudo sobre a frieza formativa por meio das narrativas animais - Telles, Rodrigo Ferreira (2020)
This doutoral thesis stablishes a dialog between education and literature to aim enlarge the perspectives over academic training. We live in a time with easy access to the information and several scientific and technological advances that could indicate overcoming inequality and social injustices. However, what is observed is a growing apathy, insensitivity and coldness that unviables the perceptions of the contradictions that organize society. Thus, we could discuss the following problem: how can we think education inside a context that coldness impacts the formation process and the indifference in one another? Aiming analysing the aesthetic-formative potencial of Franz Kafka literature, as a way to overpass this coldness. Analysing Franz Kafka writings bounds animality thematic, that can be understood as a questioning to the human being that refuses coldness practices. Kafka, tension rationality and imagination, expand a perception over reality, revealing his contradictions and paradoxes. This research has a bibliographic nature to analyse the texts “Letter to his Father” (Brief an den Vater), “The Metamorphosis” (Die Verwandlung), "The Burrow" (Der Bau), and "A Report to an Academy" (Ein Bericht für eine Akademie), for the purpose to show elements that allow comprehend human formation. The analysis is done about a dialog between the authors of Critical Theory of Society, with Max Horkheimer, Walter Benjamin, Theodor Adorno, Andreas Gruschka and commentators, Günther Anders, Elias Canetti, Gustav Janouch, Ernest Pawel, Michael Löwy and Modesto Carone. Through a constelatory proceeding, this paper presents formative categories, that emerge from Kafka`s work, and collaborate to resist to formative coldness; analysing authoritary practices that cooperates to feed coldness; points out how the lack of sensibilization process caused by coldness can end in forgetting the other; refletes the life limits that adapts to cultural and economia organization, without recognizing the contradictions caused by coldness; discusses the loss of empty experiences and scars of a pathologic time made by coldness. This way this thesis demonstrates as a result, that Kafkas literature contribute to a construction of an anti-authoritarian education, that worth the dialog and break the formative hardness that generates insensitivity and coldness; collaborates in the production of an education of sensitivity and gives greater attention to life and differences; encourages resistance to a mediocre life that adapts to social injustices; values memory as a way of not forgetting past tragedies. From the Kafkaesque writings, we can enlarge our understanding of formative categories, such as: authority, sensitivity, emancipation, memory, which are central to the creation of educational paths and which allow us to break with cold practices.